Mathematical model of selecting the elements of weather monitoring system for highway - Філь, Наталія Юріївна (Technology audit and production reserves, 2016)
Analyzes of approaches and methods of synthesis of intelligent transport systems are conducted. The implementation of intelligent transport systems will improve traffic management safety, provide reliable transportation and preservation of vehicles and cargo, and improve environmental protection. For prompt consideration of the impact of meteorological factors it should be used a system of meteorological service that will quickly decide on necessary actions in a particular stretch of road. Mathematical model of selecting the elements of weather monitoring system for highway were developed. The model refers to problems of discrete programming with Boolean variables, for their implementation it is proposed to use: for the tasks of small dimension – exhaustive search of options; for the tasks of large dimension – the method of random search. An example of selecting the elements of weather monitoring system was considered. The prospect of further research is to develop software that will automate the process of synthesis of intelligent transport systems.